2020
DOI: 10.1002/jca.21845
|View full text |Cite
|
Sign up to set email alerts
|

Current state of therapeutic apheresis and cellular therapy education for transfusion medicine fellows in the United States

Abstract: Background: Numerous conditions are responsive to therapeutic apheresis (TA) and cellular therapy (CT) treatments. Both TA and CT are two broad and diverse knowledge fields within transfusion medicine (TM). We therefore sought to survey all the TM fellowship program directors (PDs) in the United States to examine the current fellow state education in TA and CT. Methods: A 37-question survey was sent to all PDs to collect details of TA and CT training for TM fellows. Results: Responses from 29/51 (56.9%) survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The importance of dedicated apheresis medicine training as it pertains to patient safety should also be a key consideration for physician credentialing 86 . Furthermore, a survey of BB/TM program directors found that while training in progenitor/mononuclear cell collection was deemed adequate, there exists a need to bolster cellular therapy laboratory training 87 . It is also important to note, that a workforce shortage is evident in terms of cellular therapy laboratory technologists—an additional area where expansion of education, training, and certification options is needed 88,89 …”
Section: Evolving Landscape Of Therapeutic Apheresis and Cellular The...mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of dedicated apheresis medicine training as it pertains to patient safety should also be a key consideration for physician credentialing 86 . Furthermore, a survey of BB/TM program directors found that while training in progenitor/mononuclear cell collection was deemed adequate, there exists a need to bolster cellular therapy laboratory training 87 . It is also important to note, that a workforce shortage is evident in terms of cellular therapy laboratory technologists—an additional area where expansion of education, training, and certification options is needed 88,89 …”
Section: Evolving Landscape Of Therapeutic Apheresis and Cellular The...mentioning
confidence: 99%
“…86 Furthermore, a survey of BB/TM program directors found that while training in progenitor/ mononuclear cell collection was deemed adequate, there exists a need to bolster cellular therapy laboratory training. 87 It is also important to note, that a workforce shortage is evident in terms of cellular therapy laboratory technologists-an additional area where expansion of education, training, and certification options is needed. 88,89 Given the landscape of apheresis medicine and projected demand, an increased emphasis in apheresis training, as well as training in cellular therapy laboratory management and operations, is needed.…”
Section: Cellular Therapymentioning
confidence: 99%
“…Physician training in apheresis often occurs in the context of a pathology residency or transfusion medicine, hematology/oncology, and nephrology fellowships, though other pathways are also used in the United States and globally. [1][2][3][4] Educational initiatives for apheresis medicine (AM) can be complex and require attention to clinical details, as well as an appreciation of systems-based practice.…”
Section: Introductionmentioning
confidence: 99%
“…Medical directors for these services come from multiple training backgrounds such as pathology, transfusion medicine, nephrology, hematology/oncology, pediatrics, and others. Physician training in apheresis often occurs in the context of a pathology residency or transfusion medicine, hematology/oncology, and nephrology fellowships, though other pathways are also used in the United States and globally 1–4 . Educational initiatives for apheresis medicine (AM) can be complex and require attention to clinical details, as well as an appreciation of systems‐based practice.…”
Section: Introductionmentioning
confidence: 99%